TOOLS FOR INCREASING THE COMPETITIVENESS OF ENTERPRISES USING MARKETING COMMUNICATIONS - YAKUBENKO, Yuliia; KOBERNIUK, Serhii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The general composition of the marketing toolkit of enterprises is summarized. The goal of the study was the formation of tools for increasing the competitiveness of agricultural enterprises by means of marketing communications.The place of marketing communications of enterprises in the general system of the marketing mix is shown. The general criteria of competitiveness of agricultural enterprises are outlined. The directions and means of using marketing communications in order to strengthen the competitiveness of agrarian business entities have been determined, in particular by groups: (1) dissemination of communication and research policy, (2) communications in the field of product and market portfolio, (3) financial and resource planning of communications, (4) development of strategic market communications.The factors of the development of processes of interpretation of the information received by users are determined. It has been established that the competitiveness of an agricultural enterprise is a complex system category that gives a comprehensive description of its ability to oppose direct competitors, both at the current time and in the strategic perspective, in the target market segment where the enterprise's products are positioned, in order to ensure the functioning and planned development under the pressure of competition and the action of factors and conditions of the business environment.A structural and functional model for improving the policy of ensuring the competitiveness of agricultural enterprises has been developed. An arsenal of tools for increasing the competitiveness of enterprises in the agrarian sector of the national economy by means of marketing communications has been developed.
Keywords: marketing communications; agrarian business; agricultural enterprises; competitiveness; means of strengthening